The use of calcium ions instead of heat treatment for β-1, 3-glucan gelation improves biocompatibility of the β-1, 3-glucan/HA bone scaffold. (15th May 2017) - Klimek, Katarzyna; Przekora, Agata; Benko, Aleksandra; Niemiec, Wiktor; Blazewicz, Marta; Ginalska, Grazyna
Highlights: Scaffolds were prepared based on dialysis and thermal method for β-1, 3-glucan gelation. Dialysis method introduces microroughness into resultant glu/HA D scaffold. Unlike glu/HA D, thermally-prepared material (glu/HA T) has nanosmooth surface. The glu/HA D scaffold has better biocompatibility than glu/HA T. Unlike glu/HA T, glu/HA D scaffold reveals apatite formation ability in vitro . Abstract: The aim of this study was to determine which procedure for β-1, 3-glucan gelation – newly developed dialysis against calcium salt or described in the literature thermal technique – is more appropriate for fabrication of a biomaterial designed for bone tissue engineering applications. Thus, β-1, 3-glucan/hydroxyapatite scaffolds were prepared based on two different methods and their physicochemical, microstructural, and biological properties were compared. Obtained results demonstrated that unlike thermal method-prepared β-1, 3-glucan/hydroxyapatite material (glu/HA T), bone scaffold fabricated via dialysis method (glu/HA D) possessed rough surface resulting from the presence of CaCl2 precipitates as proven by SEM and EDS analysis. As a consequence, glu/HA D scaffold released Ca 2+ ions to the surrounding environment positively affecting osteoblast behaviour and biomineralization in vitro . Since glu/HA D material exhibited better bioactivity and biocompatibility compared to the glu/HA T scaffold, it may be concluded that the dialysis method is more suitable for β-1, 3-glucan/hydroxyapatite biomaterial fabrication.